2021
DOI: 10.1029/2021gl095151
|View full text |Cite
|
Sign up to set email alerts
|

Electrified Postsunrise Ionospheric Perturbations at Millstone Hill

Abstract: As the solar terminator (ST) sweeps through the Earth's atmosphere, sharp gradients in solar illumination across ST and their movement (with both supersonic and subsonic components) can induce disturbances in the atmosphere and ionosphere (Somsikov, 2011). Theoretical calculations and observational studies have focused on ST induced waves, with an emphasis on atmospheric gravity waves (GWs) associated with ST occurring in different layers of the atmosphere (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…The observed MSTIDs for the present study, however, are clearly not concentric. GWs near the terminator have often been observed, for example, Zhang, Erickson, Gasque, et al (2021) identified eastward propagating electrified TIDs during postsunrise hours, and Figure 6 shows MSTIDs near the sunset terminator at 01:30 UT on 2018-08-26 (marked as T4). To provide further contrasts of MSTIDs between storm/substorm and non-storm/substorm conditions, Figure 13 depicts sample non-storm/non-substorm MSTIDs close to the periods of the four storm events studied here.…”
Section: Discussionmentioning
confidence: 99%
“…The observed MSTIDs for the present study, however, are clearly not concentric. GWs near the terminator have often been observed, for example, Zhang, Erickson, Gasque, et al (2021) identified eastward propagating electrified TIDs during postsunrise hours, and Figure 6 shows MSTIDs near the sunset terminator at 01:30 UT on 2018-08-26 (marked as T4). To provide further contrasts of MSTIDs between storm/substorm and non-storm/substorm conditions, Figure 13 depicts sample non-storm/non-substorm MSTIDs close to the periods of the four storm events studied here.…”
Section: Discussionmentioning
confidence: 99%
“…Since first reported by Munro (1948), TIDs have been studied using many different techniques. These include ionosondes (e.g., Altadill et al., 2020; Galushko et al., 1998; Galushko et al., 2003), incoherent scatter radars (e.g., Kirchengast et al., 1996; Nicolls & Heinselman, 2007; Thome, 1964; Zhang et al., 2021), HF Doppler radars (e.g., Bristow et al., 1994; Frissell, Baker, et al., 2014; Frissell et al., 2016; Samson et al., 1989; Samson et al., 1990), broadcast AM Doppler receivers (Chilcote et al., 2015), global navigation satellite system (GNSS) total electron content (TEC) receivers (e.g., Dinsmore et al., 2021; Tsugawa et al., 2007; Zakharenkova et al., 2016), and airglow imagers (e.g., Mendillo et al., 1997; Otsuka et al., 2004; Ogawa et al., 2009). Each of these different techniques provides a unique and complementary view into understanding the nature of TIDs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhang et al. (2021) reported that the midlatitude dawn solar terminator‐excited gravity waves in the ionosphere are electrified TIDs. They suggested that the polarization electric field perturbations were embedded in TIDs though the incoherent scatter radar ion drift observations.…”
Section: Discussionmentioning
confidence: 99%